1996
DOI: 10.1111/j.0953-0673.1996.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole‐amoxycillin versus omeprazole‐amoxycillin‐clarithromycin in the eradication of Helicobacter pylori.

Abstract: These results show that dual therapy with omeprazole plus amoxycillin achieves an unacceptably low H. pylori eradication rate. Addition of clarithromycin at low dosage (250 mg b.d.) proved to be useful, achieving a high eradication rate without increasing side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…Triple therapy combining a twice daily dose of a proton pump inhibitor and two antibiotics for a week is recommended in most European countries 1 . The French Consensus Conference held in October 1995 was the first to suggest this option, for several reasons: prohibition of the use of bismuth in France; clinically unsatisfactory results of proton pump inhibitor–amoxycillin dual therapy; 3 , 4 and fear of promoting the emergence of resistance with proton pump inhibitor–clarithromycin dual therapy. The two antibiotics must be chosen from amoxycillin, clarithromycin, metronidazole or tinidazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple therapy combining a twice daily dose of a proton pump inhibitor and two antibiotics for a week is recommended in most European countries 1 . The French Consensus Conference held in October 1995 was the first to suggest this option, for several reasons: prohibition of the use of bismuth in France; clinically unsatisfactory results of proton pump inhibitor–amoxycillin dual therapy; 3 , 4 and fear of promoting the emergence of resistance with proton pump inhibitor–clarithromycin dual therapy. The two antibiotics must be chosen from amoxycillin, clarithromycin, metronidazole or tinidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Triple therapy including bismuth has never been used in France because prescription of bismuth is prohibited. Omeprazole–amoxycillin dual therapy, which has produced high eradication rates in Germany, 2 has given markedly lower rates in France, in the range of 25–50% 3 , . 4…”
Section: Introductionmentioning
confidence: 99%
“…Despite these side‐effects only two patients admitted not completing the course, and one of them still had successful eradication. The 24% incidence of any side‐effects compares very favourably with 34% in a study with clarithromycin and a proton pump inhibitor, but substituting amoxycillin for bismuth 4 . The safety of bismuth has recently been well reviewed 5 …”
Section: Discussionmentioning
confidence: 99%
“…All of the above drugs have been tried in various combinations with mixed results, but only recently has the association of amoxicillin with clarithromycin been found to be highly effective. Furthermore, the association of these two antibiotics with ranitidine [ 2] or with a proton pump inhibitor (either omeprazole or lansoprazole) [ 3–7] was proven to achieve an 82–86% eradication rate after seven days, which increased to 86–91% after 10 days [ 2, 3] and 93–95% after 14 days [ 3, 6].…”
mentioning
confidence: 99%
“…Since it has recently been suggested that even low doses of clarithromycin (i.e. 250 mg bid) are effective in eradicating H. pylori [ 6, 8–10], antibiotics were administered at the lowest recommended dosages. In order to simplify drug schedules and increase patient compliance, tinidazole was used at a dose of 500 mg twice daily, reducing to two the number of prescriptions per day.…”
mentioning
confidence: 99%